2005
DOI: 10.1007/s00330-005-2699-8
|View full text |Cite
|
Sign up to set email alerts
|

Improved pelvicalyceal visualization with multidetector computed tomography urography; comparison with helical computed tomography

Abstract: Our aim was to compare the quality of pelvicalyceal visualization on computed tomography (CT) urography using a small intravenous contrast material dose, hydration, and high-resolution multidetector CT (MDCT) with that of conventional helical CT. The test (MDCT) group (49 consecutive patients, 98 kidneys) was scanned 5 min following an intravenous bolus of 30 ml of iodinated contrast material. The control (helical CT) group (50 consecutive patients, 95 kidneys) was scanned 5 min following injection of 120-150 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…With the use of 4-detector or 8-detector row CT scanners, CT urography demonstrated satisfactory results compared with IVU in the evaluation of abnormalities involving the urothelium [10][11][12][13]. Raptopoulos et al showed a significantly improved visualization of pelvicaliceal details with MDCTU [14]. However, the sensitivity of MDCTU in the detection of uroepithelial malignancies, especially tumors of small size need to be further evaluated [15].…”
Section: Introductionmentioning
confidence: 98%
“…With the use of 4-detector or 8-detector row CT scanners, CT urography demonstrated satisfactory results compared with IVU in the evaluation of abnormalities involving the urothelium [10][11][12][13]. Raptopoulos et al showed a significantly improved visualization of pelvicaliceal details with MDCTU [14]. However, the sensitivity of MDCTU in the detection of uroepithelial malignancies, especially tumors of small size need to be further evaluated [15].…”
Section: Introductionmentioning
confidence: 98%
“…Artefacts from concentrated iodinated contrast material inside the calices and papillae may degrade the visibility of caliceal details [3,5,35]. Raptopoulos et al demonstrated that improvement of caliceal delineation is achieved by using wide windowsettings, supplemental hydration, and a contrast agent bolus of only 30 ml [35].…”
Section: Discussionmentioning
confidence: 99%
“…250 ml of saline is an empirically selected dose, which is clinically practical but unproven scientifically. Those investigators, who preferred oral supplementation of water, had administered 750 to 1000 ml within 20 min prior to scanning [18] or a volume of "six cups" during 60 minutes before scanning [35].…”
Section: Msct Urography With Saline Infusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators used similar regimes describing that 20 min prior to scanning patients ingested up to 1l of tap water [16][17][18] or "six cups" of water during 60 min before scanning. [19] Saline infusion might be used as an alternative. [6,20,21] However, some studies showed no particular benefit for saline injection or administration of oral water.…”
Section: Discussionmentioning
confidence: 99%